Printed reflectarray antennas investigation based on the finite-infinite structures model - Ballandovich, S. V.; Kostikov, G. A.; Sugak, M. I.; Antonov, Y. G. (2016 ElConRusNW : proceedings of the 2016 IEEE North West Russia Section Young Researchers in Electrical and Electronic Engineering Conference : February 2-3, 2016, St. Petersburg Russia, 2016)
A printed-reflectarray antennas model based on finite-infinite structures is described. A bandwidth dependence on various antennas parameters is investigated with given mathematical model. In addition, some specific features of designing process of large-aperture reflectarray antennas are described.